Teachers’ practice of mathematical representation, and its relationship to the preschooler’s utilization of it in expressing mathematical ideas - Al-Owaidh, Reem Khlifa; Khomais, Sama Fouad (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to uncover the relationship between teachers' level of practice of mathematical representation and the preschooler’s utilization of it in expressing mathematical ideas. The study followed the descriptive correlational approach and used two observation forms, one for the teacher and one for the child. The sample consisted of (15) preschool teachers working in kindergarten schools that use a mathematics program in their daily curriculum in Al-Ahsa city, and (120) children in their classrooms. The data was statistically analyzed using mean, standard deviations, and Pearson correlation coefficient to find the relationship. The results indicated a statistically significant positive correlation between teachers' practices of mathematical representation and the utilization of children in expressing mathematical ideas. The study also revealed that the level of teachers' practices of mathematical representation was low, as well as the level of children's utilization of mathematical representation in expressing their ideas. Based on the results, the study recommends providing professional development programs for early childhood teachers that include methods of using mathematical representations in presenting and explaining mathematical concepts. Sufficient time and developmentally appropriate activities should be provided for all children to engage in mathematical activities in general, and mathematical representation in particular.
Keywords: Teaching practices; mathematical representation; preschool children; early mathematics learning